Pengembangan Instrumen Penilaian unjuk Kerja dengan Model Peer Asssessment System untuk Mata Pelajaran Penjasorkes pada Pokok Bahasan Permainan Bola Voli - Lalu Hasan Ashari; Djuniadi Djuniadi (Universitas Pendidikan Mandalika (UNDIKMA), 2015)
This study aims to develop an authentic assessment instrument on a volleyball game with a peer assessment system approach. This research uses research and development method. Data analysis is done by following mechanism. First the validity of the content of the instrument by the judgment ekspert analyzed using Aiken formula, obtained the validity of 0.90 count. Both test data of the validity of grain (empirical), analyzed using Product Moment formula obtained correlation coefficient of all instrument items bigger than table price with significant 5% tarap, with the meaning of all instrument items valid. The three test data of internal consistency reliability of the instrument, analyzed using Alpha Cronbach formula, obtained the calculated value of 0.82, which stated that the reliability is very high. The five practicalities of the instrument were analyzed with the T Score formula, obtained by an average score of 50, which means that the instrument is classified as practical for students. This means that the results of the research and development of the performance appraisal instrument with the peeer assessment system model in the developed volleyball game have fulfilled the validity, reliability and practical requirements, and are expected to be an evaluation tool that can be used (alternativ) by the teacher of the school in primary and secondary schools (Junior high school, high school).